“SOCIODEMOGRAPHIC, CLINICAL CHARACTERISTICS & COMPLICATIONS AMONG ONCOLOGICAL PATIENTS WITH CHEMOPORTS & REASONS FOR REMOVAL OF CHEMOPORTS: AN OBSERVATIONAL STUDY IN A TERTIARY CARE CENTRE IN WESTERN RAJASTHAN” - Suresh Kumar; Ram Dayal; Vijay Verma; Sunita Malviya; Kishna Ram (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
: The management of a cancer patient demands stable venous access that can be utilized for giving chemotherapy, administering blood products, antibiotics and fluid replacement therapy. The use of long-term venous access devices or central venous catheters can also alleviate patient anxiety associated with repeated venipunctures. Chemo ports, also known as implantable ports or venous access devices, have become an increasingly common solution to facilitate chemotherapy administration. These devices have become the cornerstone of modern medical therapy in oncological practice.Material and method: This observational study was performed on 100 patients of various oncological diagnosis who underwent chemoport insertion for purpose of chemotherapy delivery in surgical departments of DR.S.N. Medical College, Jodhpur from May 2022 to October 2024.Result: Most common age group pf patients was 40-60 years with a female predominance & breast cancer as the most common oncological diagnosis in patients who underwent chemoport insertion in our study. The mean duration of port in situ was 382.5 days. Complications are significantly varied, with septic complications being the most common, followed by thrombosis. Most of the complications were managed by removal of chemoport and some being managed conservatively. All the studied parameters were comparable with previous studies.Conclusion: This study meticulously examines the complications associated with chemoports, including infections, thrombosis, mechanical issues, and port-related pain, documenting their incidence and severity. The study also underscores the critical role of chemoports in oncological care, highlighting their effectiveness in reducing the necessity for multiple painful venipunctures to administer chemotherapeutic agents by minimizing the pain and anxiety associated with cancer treatment & significantly enhancing the quality of life.